Income Analysis of Lawi-Lawi (Coulerpa sp) in Laikang Village,Mangarabombang Sub-District, Takalar District - Udin, Risma; Fakhriyyah, Sitti; Cangara, Arie Syahruni (PONGGAWA : Journal of Fisheries Socio-Economic, 2023)
Seaweed has become a prima donna commodity for coastal communities, considering its positive contribution to the workforce and increasing income. Types of seaweed that have potential but have not been widely cultivated are Caulerpa sp. with the local names 'lawi-lawi' (Sulawesi) and 'Latoh' (Java). Lawi-lawi is widely known by the coastal community because several types of seaweed are used as daily natural food ingredients in South Sulawesi and are used for medical purposes because they contain antioxidants. Takalar Regency is the center of Lawi-lawi seaweed incubator, where development clusters are spread throughout the sub-district. One of the sub-districts that is the center for the development of Lawi-lawi seaweed is Mangarabombang District. some people in Laikang Village make a living as cultivators of lawi-lawi. Lawi-lawi cultivation activities in this village have been going on since 2011 and continue to grow until now. The purpose of this study was to determine the investment and income of lawi-lawi cultivators. The results showed that the average cost of cultivation of lawi-lawi (Caulerpa Sp) in Laikang Village, Mangarabombang District, Takalar Regency was IDR 8.397.500, the total annual income was IDR 8 .397.500 IDR. 147.600.000, total monthly income of  IDR. 16.132.427.